Enhancing Rabbit Growth Performance: The Impact of Genotype and Probiotic Supplementation - Osti, Komal Laxmi; Osti, Netra Prasad; Shah, Manoj Kumar; Salma, Ummay; Miah, Abdul Gaffar (International Journal of Applied Sciences and Biotechnology, 2025)
This study examines the effects of probiotic supplementation and genotype on the growth performance of post-weaned rabbits. A total of 24 rabbits, equally divided between California White and Soviet Chinchilla breeds, were assigned to three dietary treatments: T1 (control, no probiotics), T2 (1g probiotics/kg feed), and T3 (2g probiotics/kg feed). The experiment lasted 14 weeks, during which body weight, weight gain, feed intake, and feed conversion efficiency were monitored. Results indicated that rabbits in the T3 group achieved the highest body weight gain and feed conversion efficiency compared to T1 and T2. California White rabbits exhibited superior growth performance over Soviet Chinchilla rabbits. Probiotic supplementation enhanced digestion, improved nutrient absorption, and contributed to more efficient feed utilization, leading to better overall growth and health outcomes. The ability of probiotics to support gut integrity and immune function was evident in the improved physiological responses observed in probiotic-supplemented groups. Additionally, no mortality was observed, highlighting the potential of probiotics in reducing disease susceptibility and promoting overall well-being. These findings underscore the potential of probiotics as a natural, cost-effective strategy to improve rabbit growth performance, enhance feed efficiency, and support sustainable rabbit farming. The study also emphasizes the importance of genotype in determining growth outcomes, with California White rabbits demonstrating superior performance. Future research should explore the broader implications of probiotics in livestock, particularly in ruminants like buffaloes, to optimize meat and milk production, reduce antibiotic dependence, and enhance overall farm profitability. Int. J. Appl. Sci. Biotechnol. Vol 13(1): 52-57.